Telemarketing and the Door to Door Sales Act 1967 - Tokeley, Kate (Victoria University of Wellington Law Review, 2006)
The Door to Door Sales Act 1967 was intended to protect consumers from the sales pressure applied by sellers knocking on their door in an attempt to sell their products. In recent times sellers have adopted new methods of marketing their products, including the practice of telemarketing. In the recent case of Commerce Commission v Telecom Mobile Ltd the Court of Appeal concluded that the particular telemarketing activities undertaken by Telecom Mobile were covered by the Door to Door Sales Act 1967. This article analyses the difficulties and uncertainty of applying the outdated Act to the practice of telemarketing. Some contracts made as a result of telemarketing are covered by the Act and other contracts are not. The article argues that this arbitrary approach is unsatisfactory and that the law should be reformed so that the Act expressly covers all contracts that result from an unsolicited telemarketing phone call.